Factors affecting Muzakki’s interest in paying agricultural Zakat in Sidenreng Rappang Regency - Katman, Muhammad Nasri; Rahmawati, Rahmawati; Nur, Muhammad; Yunus, Ayu Ruqayyah; Hikmah, Nur (Technium Social Sciences Journal, 2022)
Objectives-This study aims to determine the factors that influence the interest of muzakki to pay agricultural zakat in Sidenreng Rappang district. Methodology-This type of research is a quantitative approach with a sampling technique using the convenience sampling method. The number of samples used in this study was 41 respondents. The data collection method in this study used a questionnaire. Testing the results of the questionnaire using validity analysis and reliability analysis. As for the data analysis in this study using the classical assumption test, multiple regression analysis, F test, t test, and the coefficient of determination test. The results of the study show that partially the variables of Faith, understanding of zakat, socialization income and trust have an effect on the variable interest of muzakki paying agricultural zakat, social care variables, self-satisfaction and the environment have no significant effect on the variable of interest of muzakki paying agricultural zakat, simultaneously the variable Faith , Understanding of zakat, income socialization of social care, self-satisfaction and the environment and trust have a significant influence on the variable muzakki interest in paying zakat.